If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 4x = x Solving 18 + 4x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 18 + 4x + -1x = x + -1x Combine like terms: 4x + -1x = 3x 18 + 3x = x + -1x Combine like terms: x + -1x = 0 18 + 3x = 0 Add '-18' to each side of the equation. 18 + -18 + 3x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 3x = 0 + -18 3x = 0 + -18 Combine like terms: 0 + -18 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| x=23+6(-3) | | -6=-2n-3/4 | | x-1/4=3/4 | | (98-2*21)/2 | | 2b-15=a | | 2a+45=5a | | 1.5x+4.23=3.56x+2.12 | | 15-2b=a | | x+6=-7x-26 | | -6(23+6y)-5y=-15 | | 2*21+2*28= | | f(-3)=-8 | | 2x^2+3=14 | | 30x+10(x+0.35)=4135 | | 3a+7-11-9a= | | 2(21+28)= | | -9x-4=3 | | 7w-11= | | 7w+11= | | -3y+42=6 | | W-56=560 | | 7x+10=9x+2 | | 2*a*a*3=66 | | 6=s/3 | | m(m-3)-2n(m-4)=-(m^2-4m)+6 | | 10x-4x=35 | | 2e-12=7e-8 | | 3a-5b=15-2a | | 16x+20=52 | | 2x-2=x-2 | | 4(3a+2b)=4b-3c | | a=15-2b |